Bank credit portfolio allocation in pre and post Covid times: The power of inherent risks - David M. Ndwiga (Kenya Bankers Association (KBA), 2023)
The study seeks to determine how the bank credit allocation has evolved in pre - covid, covid and post covid era amid possible uncertainties. Study focused on credit risk, liquidity risk, industry competition and operating efficiency for 2010 - 2021 period. Panel Autoregressive Distributed Lag and panel Generalized Method of Moments were applied for bank level data while sectoral level Autoregressive Distributed Lag models were applied for sectoral analysis. The study found credit, liquidity, covid are all negatively related to bank credit allocation. In addition, interaction of covid with credit and liquidity risks reveal that the effect of liquidity risk is more pronounced. Recovery era simulation posits that personal household sector would register the highest allocation with real estate sector allocation being last. The study calls for more vigilance in the post pandemic times as credit risk is likely to reveal itself amid relaxation in loan reclassification. Further, a more proactive monetary policy is advocated for to address the liquidity distribution challenges.
Keywords: 330